Copper-based adsorbent and application thereof in glove box purification column
Through the preparation of copper-based adsorbents, combined with supergravity and co-precipitation technology, the problem of high acid gas pollution and maintenance costs during the regeneration of the purification column in the vacuum glove box is solved, and the effect of efficient deoxygenation and low cost is achieved, which significantly improves the effect of significantly deoxygenation and low cost. The stability and life of the adsorbent are achieved.
Patent Information
- Application Number
- CN202411483638.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-17
AI Technical Summary
The acid gas absorbed by the purification column in the vacuum glove box during the regeneration process leads to environmental pollution, and the maintenance cost of replacing the purification column is high, and the change in gas pressure leads to waste of inert gas, which requires improving the performance and life of the adsorbent to reduce costs.
Copper-based adsorbent is used to prepare a loaded adsorbent through the reaction of precipitant and active metal salt. Combined with supergravity and co-precipitation technology, mold release agent, glidant and binder are added to improve bulk density and molding difficulty. It is suitable for It is used to purify the column in the glove box, with short preparation cycle, low cost and good deoxygenation performance.
It achieves the improvement of the stability and deoxygenation performance of the adsorbent under short preparation cycles and low costs, extends the life of the adsorbent, reduces maintenance costs, reduces gas waste, and significantly improves the purification effect.
Smart Images

Figure CN119318937A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a copper-based adsorbent and application thereof in a glove box purification column, belonging to the technical field of catalysts containing metals or metal oxides. Background Art
[0002] A vacuum glove box is a laboratory device that fills a box with high-purity inert gas and circulates and filters out the active substances in it. Glove boxes are widely used in high-tech research fields and production processes such as medicine, biology, chemistry and chemical engineering, nuclear energy, lithium batteries, sodium batteries, and mechanical processing.
[0003] After long-term use of the vacuum glove box, the oxygen content and water content usually increase. The purification material inside the purification column can be directly regenerated and restored by regeneration means. If the regeneration effect is not good, the purification column can only be replaced as a whole. When the purification material is regenerated and restored, the acidic gas absorbed by the purification column during the purification process will be discharged together with the regeneration tail gas, causing pollution to the external environment. If the purification column is replaced as a whole, the maintenance cost is high, and when the glove box is operated again, the gas pressure in the glove box will change, and the inert gas in the cylinder will be replenished to maintain the pressure balance, causing waste. Therefore, improving the performance and life of the core material adsorbent in the purification column is very beneficial to reducing costs. Summary of the invention
[0004] In view of this, the present application first provides a copper-based adsorbent, which not only has good adsorption activity and good deoxygenation effect, but also has the advantages of short preparation cycle and good stability.
[0005] Specifically, the present application is implemented through the following scheme:
[0006] A copper-based adsorbent is prepared by using a precipitant and an active metal salt as raw materials through the following steps:
[0007] Step 1: mixing and dissolving an active metal salt with a solvent to obtain a mixed metal salt solution, wherein the metal ion concentration in the mixed metal salt solution is 0.5 to 2 mol / L.
[0008] The active metal salt includes copper salt, and any one or more of magnesium salt, zinc salt, and aluminum salt;
[0009] Step 2: Mix and dissolve the precipitant and solvent to obtain a precipitant solution, wherein the concentration of the precipitant solution is 1 to 2 mol / L.
[0010] The precipitant is one or a mixture of sodium carbonate, sodium hydroxide and sodium bicarbonate;
[0011] Step 3: The mixed metal salt solution reacts with the precipitant solution to obtain a precursor, which is then separated, dried, and calcined to obtain a supported copper-based adsorbent with a size of φ1.8-6 mm.
[0012] The added molar ratio of the mixed metal salt solution to the precipitant solution is 1:1 to 1.8.
[0013] The above scheme uses copper salt as one of the active components, and combines it with magnesium salt, zinc salt, aluminum salt, etc. to form a mixed metal salt solution, which is then mixed with a solution formed by one or more alkaline precipitants and reacted to obtain a precursor. After further centrifugation or filtration and washing to complete separation, it is dried, calcined, and formed to obtain a loaded copper-based adsorbent. The obtained copper-based adsorbent not only has a short preparation cycle, but also has uniform quality and good deoxygenation performance.
[0014] Further, as a preference:
[0015] In step one:
[0016] The active metal salt is any one, any two or a combination of two or more of the nitrate, sulfate, silicate and acetate of the active metal.
[0017] The mixed metal salt solution is further added with a noble metal salt, which is any one of platinum salt, ruthenium salt, and palladium salt, or a combination of two or more thereof. More preferably, the noble metal salt is one, two, or a combination of two or more of a nitrate or sulfate of a noble metal.
[0018] The solvent is any one of water, ethanol, methanol and acetone.
[0019] In step 2:
[0020] The solvent is any one of water, ethanol, methanol and acetone.
[0021] In step three:
[0022] The pH of the solution obtained by mixing the mixed metal salt solution and the precipitant solution is 7-9.
[0023] The drying temperature is 60-100° C., and the drying time is 12-24 hours. Drying can be performed in an oven.
[0024] The calcination temperature is 260-350° C., and the drying time is 1-3 hours. The calcination can be performed in a muffle furnace.
[0025] A release agent and / or a flow aid and / or a binder are added to the precursor and / or the supported copper-based adsorbent to improve the fluidity of the precursor and the copper-based adsorbent and the bonding force between the particles. The amount of the release agent added is 1-2% of the total mass of the precursor and / or the supported copper-based adsorbent, the amount of the flow aid added is 1-2% of the total mass of the precursor and / or the supported copper-based adsorbent, and the amount of the binder added is 1-1.5% of the total mass of the precursor and / or the supported copper-based adsorbent. The release agent is graphite and / or magnesium stearate, the flow aid is one or a mixture of microcrystalline cellulose and fumed silica, and the binder is one or a combination of two or more of microcrystalline paraffin, stearic acid, and polypropylene.
[0026] In the above scheme, the reaction can be carried out in a supergravity reactor or in a coprecipitation reactor. When a supergravity reactor is used as a reaction device, the core control parameter of the supergravity reactor is the rotation speed, which is preferably controlled at 1800-2800 r / min, and the reaction time is 2-10 hours. When a coprecipitation reactor is used, the reaction time is preferably controlled at 10-20 hours.
[0027] After the reaction, it is suitable to further treat by aging or the like to obtain an ideal precursor. The aging time is preferably controlled at about 2 hours, and generally, an ideal precursor can be obtained within no more than 2 hours.
[0028] The precipitant solution and the mixed metal salt solution are added to the reaction process. At this time, the reaction temperature can be roughly controlled at 30-80°C. At this temperature, the mixed metal salt solution and the precipitant solution complete the dissolution and preheating process of each other to ensure uniform precursor formation.
[0029] The second purpose of the present application is to provide an application of the above-mentioned copper-based adsorbent, that is, the application of the copper-based adsorbent in a glove box purification column, wherein the application temperature is room temperature, the regeneration temperature is 200-400°C, and the regeneration pressure is normal pressure.
[0030] Compared with the prior art, the copper-based adsorbent of the present application is a supported adsorbent, which has the following beneficial effects:
[0031] (1) The copper-based adsorbent provided by the present invention uses a precipitant and a mixed metal salt containing a copper salt as main raw materials, and the copper-based adsorbent is obtained by reaction. It not only has a short production cycle, low cost, simple process operation, small scale-up effect, and stable batch production; the obtained supported copper-based adsorbent also has the advantages of good adsorption activity and strong stability, and has good application prospects.
[0032] (2) The present invention synthesizes a precursor of a supported copper-based adsorbent and adds a certain amount of additives, such as graphite and / or magnesium stearate as a demoulding agent, a mixture of one or two of microcrystalline cellulose and fumed silica as a flow aid, and a combination of one or more of microcrystalline paraffin, stearic acid, and polypropylene as a binder, so that the bulk density of the supported copper-based adsorbent is increased, the molding difficulty is reduced, and demoulding is easier. More mass of adsorbent can be loaded in a limited purification column volume, thereby improving the single-pass purification capacity.
[0033] (3) The present invention adopts ultra-gravity, co-precipitation technology and other methods to carry out the reaction to achieve the preparation of the adsorbent, which can enhance the mass transfer process in the reaction, can significantly shorten the reaction time, avoid the amplification effect, and is conducive to large-scale industrial production and rapid product upgrading and iteration. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0035] Figure 1 This is a SEM image of the copper-based adsorbent prepared in Example 1; DETAILED DESCRIPTION
[0036] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application clearer, the technical solutions in the embodiments of this application will be further described in detail below in conjunction with the drawings in the embodiments of this application. It should be understood that the specific embodiments described herein are only used to explain this application and are not used to limit the technical solutions of this application. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0037] In the following embodiments:
[0038] (1) The ultra-gravity reactor uses a rotating packed bed, and the packing is a mesh packing. The method of use can refer to CN105080446B.
[0039] (2) Specific surface area test method of the prepared copper-based adsorbent:
[0040] Sample pretreatment conditions: weigh 0.2 g of supported copper-based adsorbent sample and place in vacuum (less than 10 - 5 Torr) for 12 h.
[0041] Test conditions: N2 was used as the adsorbent and the test was carried out at -196°C.
[0042] The total specific surface area of the samples was calculated using the BET equation.
[0043] Several specific copper-based adsorbent product preparations are provided below.
[0044] Example 1
[0045] The preparation process of the copper-based adsorbent in this embodiment is as follows:
[0046] (1) Take 189.8 g of copper sulfate, 2.3 g of zinc sulfate, 125.7 g of magnesium sulfate, and 0.038 g of palladium sulfate in a beaker, and add pure water to prepare a mixed metal salt solution with a total metal ion concentration of 1.28 mol / L.
[0047] (2) Sodium carbonate is added to pure water to prepare a 1.5 mol / L solution, stirred to dissolve, and heated in a water bath until the solution temperature rises to 60° C. to obtain a precipitant solution.
[0048] (3) The rotation speed of the high-gravity reactor is adjusted to 1800 r / min. When the high-gravity field is stable, a peristaltic pump is used to simultaneously add a mixed metal salt solution and a precipitant solution to the high-gravity reactor. The speed of the mixed metal salt and the precipitant is 2 L / min. The pH of the suspension obtained by the reaction is controlled to be around 7. The suspension at the outlet of the high-gravity reactor is transferred to the aging process. After aging for 2 hours, the precipitate obtained by aging is filtered and centrifuged with deionized water until the supernatant is neutral. The solid is dried in an oven at 80°C for 12 hours. The solid obtained is the precursor of the supported copper-based adsorbent. The precursor is placed in a muffle furnace and heated to 350°C for calcination for 1.5 hours. The calcined product is transferred to a mixer and graphite is added for molding to obtain a molding size of The finished product. Graphite is used as a demoulding flow aid, and the added amount is 2% of the mass of the calcined product.
[0049] Example 2
[0050] The preparation process of the copper-based adsorbent in this embodiment is as follows:
[0051] (1) Take 146.9 g of copper nitrate, 1.9 g of zinc nitrate, and 111.1 g of magnesium nitrate in a beaker, and add pure water to prepare a mixed metal salt solution with a total ion concentration of 1 mol / L.
[0052] (2) Sodium carbonate and sodium hydroxide are added to pure water in a mass ratio of 1:1 and a solution concentration of 2 mol / L, stirred and dissolved, and then heated in a water bath until the solution temperature rises to 60° C. to obtain a precipitant solution.
[0053] (3) The rotation speed of the high-gravity reactor was adjusted to 2800 r / min. When the high-gravity field was stable, a peristaltic pump was used to simultaneously add a salt solution and a precipitant solution to the reactor. The speed of the mixed metal salt and the precipitant was 1.5 L / min. The pH of the solution after the reaction was controlled at about 7. The suspension at the outlet of the high-gravity reactor was passed into the aging reactor and circulated for 1 min before stopping. The precipitate was centrifuged and washed with deionized water until the supernatant was neutral. The precipitate was dried in an oven at 60°C for 12 h. The solid obtained was a supported copper-based adsorbent precursor. The precursor was placed in a muffle furnace and heated to 300°C and calcined for 1.5 h to obtain a supported copper-based adsorbent powder.
[0054] The calcined product was transferred to a mixer and magnesium stearate was added for molding to obtain a finished product with a molding size of φ=5*5 mm. Magnesium stearate was used as a flow aid, and the added amount was 1.5% of the mass of the calcined product.
[0055] Example 3
[0056] The preparation process of the copper-based adsorbent in this embodiment is as follows:
[0057] (1) Take 102.5 g of copper sulfate, 1.3 g of zinc sulfate, and 105.8 g of magnesium sulfate in a beaker, and add pure water to prepare a mixed metal salt solution with a total ion concentration of 0.8 mol / L.
[0058] (2) Sodium carbonate was added to pure water to prepare a 1.2 mol / L solution, and after stirring to dissolve, the solution was heated in a water bath to raise the temperature to 70° C. to obtain a precipitant solution.
[0059] (3) Adjust the speed of the high-gravity reactor to 1800r / min, wait until the high-gravity field is stable, use a peristaltic pump to add salt solution and precipitant solution to the reactor at the same time, the speed of mixing metal salt and precipitant is 2L / min, and the pH of the solution after the reaction is controlled at about 7. The suspension at the outlet of the high-gravity reactor is passed into the aging reactor and stirred for 2 hours, the temperature is maintained at 50°C, the precipitate is centrifuged and washed with deionized water until the supernatant is neutral, and the precipitate is dried in an oven at 80°C for 12 hours. The solid obtained is a supported copper-based adsorbent precursor. The precursor is placed in a muffle furnace and heated to 300°C for calcination for 1.5 hours to obtain a supported copper-based adsorbent.
[0060] The calcined product is transferred to a mixer and microcrystalline wax is added for molding to obtain a finished product with a molding size of φ=5*5mm. The microcrystalline wax is used as a binder to increase the particle size, and the addition amount is 1.5% of the mass of the calcined product.
[0061] Example 4
[0062] The preparation process of the copper-based adsorbent in this embodiment is as follows:
[0063] (1) Take 110.2 g of copper nitrate, 1.5 g of zinc nitrate, and 100 g of magnesium nitrate in a beaker, and add pure water to prepare a mixed metal salt solution with a total ion concentration of 0.85 mol / L.
[0064] (2) Sodium carbonate was added to pure water to prepare a 1.5 mol / L solution, and after stirring to dissolve, the solution was heated in a water bath to raise the temperature to 60° C. to obtain a precipitant solution.
[0065] (3) The reaction was carried out in a coprecipitation reactor, and the speed of mixing the metal salt and the precipitant was 1 L / min. The pH of the solution after the reaction was controlled at about 7. The suspension at the outlet of the coprecipitation reactor was introduced into an aging reactor and stirred for 12 hours, and the temperature was maintained at 50°C. The precipitate was centrifuged and washed with deionized water until the supernatant was neutral. The precipitate was dried in an oven at 60°C for 12 hours. The solid obtained was a supported copper-based adsorbent precursor. The precursor was placed in a muffle furnace and heated to 300°C and calcined for 1.5 hours to obtain a supported copper-based adsorbent.
[0066] The calcined product was transferred to a mixer and graphite was added for molding to obtain a finished product with a molding size of φ=5*5 mm. The graphite was used as a mold release agent, and the added amount was 2% of the mass of the calcined product.
[0067] Example 5
[0068] The preparation process of the copper-based adsorbent in this embodiment is as follows:
[0069] (1) Take 110.2 g of copper nitrate, 1.5 g of zinc nitrate, 100 g of magnesium nitrate, and 0.003 g of platinum nitrate in a beaker, add methanol to prepare a mixed metal salt solution with a total ion concentration of 0.85 mol / L (stir and dissolve at room temperature).
[0070] (2) Sodium carbonate and sodium bicarbonate (1:0.5) are added to pure water to prepare a 1.5 mol / L solution, and the solution is stirred and dissolved to obtain a precipitant solution.
[0071] (3) The reaction was carried out in a coprecipitation reactor, and the speed of mixing the metal salt and the precipitant was 1 L / min. The pH of the solution after the reaction was controlled at about 7. The suspension at the outlet of the coprecipitation reactor was introduced into an aging reactor and stirred for 12 hours, and the temperature was maintained at 30°C. The precipitate was centrifuged and washed with deionized water until the supernatant was neutral. The precipitate was dried in an oven at 60°C for 12 hours. The solid obtained was a supported copper-based adsorbent precursor. The precursor was placed in a muffle furnace and heated to 300°C and calcined for 1.5 hours to obtain a supported copper-based adsorbent.
[0072] The calcined product was transferred to a mixer and molded by adding microcrystalline cellulose to obtain a molded product with a size of The finished product. Microcrystalline cellulose is used as a flow aid, and the added amount is 1% of the mass of the calcined product.
[0073] Product characterization:
[0074] (1) SEM test
[0075] The copper-based adsorbent prepared in Example 1 was subjected to SEM testing, and the results were as follows: Figure 1 As shown: the prepared copper-based adsorbent product is in an amorphous state.
[0076] (2) BET characterization
[0077] The copper-based adsorbents prepared in Examples 1 to 5 were subjected to BET characterization, and the results are shown in Table 1.
[0078] Table 1: BET characterization data of the copper-based adsorbent provided in this application
[0079]
[0080] Performance Testing:
[0081] The copper-based adsorbents prepared in Examples 1-5 were respectively applied to a Mikaelona vacuum glove box (such as the ADVANCED series), and the specific operation methods were as follows:
[0082] 1. Turn off the water oxygen probe;
[0083] 2. Turn off the loop;
[0084] 3. Ensure that there is enough working gas (at least half a bottle);
[0085] 4. Open regeneration, and a window will appear asking “Regeneration”, click yes;
[0086] 5. A window "Check whether the mixed gas is OK" appears. At this time, open the mixed gas (argon 95%, hydrogen 5%), and adjust the pressure of the sub-meter to 0.03-0.04MPa until gas is discharged from the exhaust pipe (if no gas is discharged, the pressure can be increased until gas is discharged and then adjusted back to 0.03-0.04MPa); then click yes;
[0087] 6. Regeneration begins at this time and lasts for 16 hours.
[0088] The statistical results of adsorption performance and regeneration performance are shown in Table 2 and Table 3.
[0089] Table 2: Regeneration performance data of copper-based adsorbents provided in this application (molding size is )
[0090] Oxygen concentration before regeneration ppm Oxygen concentration after regeneration ppm Example 1 600 ≤0.5 Example 2 600 ≤5 Example 3 600 ≤8 Example 4 600 ≤15 Example 5 600 ≤7 R3-11G 600 ≤1 .
[0091] Table 3: Particle tap density data of copper-based adsorbents provided in this application (molding size is )
[0092] Particle tap density (g / mL) Example 1 0.75 Example 2 0.64 Example 3 0.72 Example 4 0.42 Example 5 0.68 .
[0093] analyze:
[0094] Combining Table 1, Table 2 and Table 3, we can see that:
[0095] The mixed salt concentration is preferably 1.28 mol / L, the precipitant concentration is preferably 1.5 mol / L, and the high gravity reactor speed is preferably 1800 r / min, at which time the copper-based adsorbent prepared has the best BET performance. The copper-based adsorbent prepared in Example 1, which contains both active metal salts and noble metal salts and is reacted in a high gravity reactor, has the largest specific surface area, followed by Example 5, which also contains active metal salts and noble metal salts but is reacted by coprecipitation, and then Example 2.
[0096] In terms of regeneration performance, the finished product obtained in Example 1 can reduce the oxygen concentration after circulation in the glove box from 600 ppm to below 0.5 ppm, followed by Example 2 and then Example 5. Taking Example 1 and Example 2 as the comparison, both of which use nitrate + ultra-gravity reactor, but the activity of the adsorbent obtained in Example 1 is much better than that in Example 2, indicating that the addition of precious metals has a significant effect on improving the activity of the adsorbent.
[0097] In the above scheme, although the mixed metal salt solution of Example 5 also contains active metal salts and noble metal salts at the same time, due to the use of a coprecipitation reactor for reaction, its BET characterization parameters and regeneration performance are significantly lower than those of Example 1, but the specific surface area and regeneration performance are still higher than those of Example 4 which also uses a coprecipitation reactor but does not contain noble metal salts. This shows that the use of an ultra-gravity reactor is more conducive to the mass transfer process in the present application scheme, the reaction rate is faster, and the finished product effect is more uniform. In terms of reaction time, it is manifested as follows: the reaction time in the coprecipitation reactor is much longer than the reaction time in the ultra-gravity reactor.
[0098] Compared with Example 4 which uses the traditional coprecipitation method for reaction, Examples 1, 2, and 3 which use the supergravity reactor for reaction have higher oxygen removal performance. This may be because the adsorbent produced in Example 4 has a smaller bulk density. Under a fixed volume, the mass of adsorbent loaded into the purification system is small, so on the basis of the same volume, its deoxygenation performance is lower. And because the supergravity technology can be produced continuously, the reaction time is greatly reduced, which is conducive to industrial production. It can be seen that the deoxygenation effect is achieved by the composition and ratio of the mixed metal salt and the coordination of the preparation method.
[0099] By comparing with the commercial adsorbent (R3-11G, i.e., BASF copper catalyst R3-11G), the adsorbent prepared in Example 1 can reach and exceed the level of common commercial adsorbents on the market. It is inexpensive, can be produced quickly, and has low difficulty in expanding production. It is an important component of the glove box purification system.
[0100] The above-mentioned embodiments only express several feasible implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention, and the embodiments are not used to limit the scope of protection in the claims of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and all equivalent implementations or changes that do not depart from the present invention should be included in the technology of the present invention.
Claims
1. A copper-based adsorbent, characterized in that The precipitant and active metal salt are used as raw materials and prepared by the following steps: Step 1: mixing and dissolving an active metal salt with a solvent to obtain a mixed metal salt solution, wherein the metal ion concentration in the mixed metal salt solution is 0.5-2 mol / L. The active metal salt includes copper salt, and any one or more of magnesium salt, zinc salt, and aluminum salt; Step 2: Mix and dissolve the precipitant and solvent to obtain a precipitant solution with a concentration of 1-2 mol / L. The precipitant is one or a mixture of sodium carbonate, sodium hydroxide and sodium bicarbonate; Step 3: The mixed metal salt solution reacts with the precipitant solution to obtain a precursor, which is then separated, dried, and calcined to obtain a supported copper-based adsorbent with a size of φ1.8-6 mm. The added molar ratio of the mixed metal salt solution to the precipitant solution is 1:1 to 1.
8.
2. A copper-based adsorbent according to claim 1, characterized in that: The active metal salt is one or a combination of two or more of the nitrate, sulfate, silicate and acetate of the active metal.
3. A copper-based adsorbent according to claim 1, characterized in that: In step 1, a noble metal salt is further added to the mixed metal salt solution, and the noble metal salt is any one of platinum salt, ruthenium salt, and palladium salt, or a combination of two or more thereof.
4. A copper-based adsorbent according to claim 3, characterized in that: The noble metal salt is one or a combination of two or more noble metal nitrates and sulfates.
5. A copper-based adsorbent according to claim 1, characterized in that: In step three, any one or more of a release agent, a flow aid, and a binder are also added to the precursor and / or the supported copper-based adsorbent, the amount of the release agent added is 1 to 2% of the total mass of the precursor and / or the supported copper-based adsorbent, the amount of the flow aid added is 1 to 2% of the total mass of the precursor and / or the supported copper-based adsorbent, and the amount of the binder added is 1 to 1.5% of the total mass of the precursor and / or the supported copper-based adsorbent.
6. A copper-based adsorbent according to claim 1, characterized in that: In step 3, the pH of the solution obtained by mixing the mixed metal salt solution and the precipitant solution is 7-9.
7. A copper-based adsorbent according to claim 1, characterized in that: The drying temperature is 60-100°C, and the drying time is 12-24 h; the calcination temperature is 260-350°C, and the drying time is 1-3 h.
8. A copper-based adsorbent according to any one of claims 1 to 7, characterized in that: The reaction is carried out in a supergravity reactor, the rotation speed of the supergravity reactor is 1800-2800 r / min, and the reaction time is 2-10 h.
9. A copper-based adsorbent according to any one of claims 1 to 7, characterized in that: The reaction is carried out in a coprecipitation reactor, and the reaction time is 10 to 20 hours.
10. Use of the copper-based adsorbent according to claim 1 in a glove box purification column, characterized in that: The copper-based adsorbent is applied in a glove box, the application temperature is room temperature, the regeneration temperature is 200-400° C., and the regeneration pressure is normal pressure.
Citation Information
Patent Citations
A multi-stage feed supergravity liquid-liquid reactor device and its application
CN105080446B
Cited By
Preparation method and application of hydrotalcite-like copper-based methanol reforming hydrogen production catalyst
CN118162140A